Stereospecific effects of ginsenoside 20-Rg3 inhibits TGF-beta 1-induced epithelial-mesenchymal transition and suppresses lung cancer migration, invasion and anoikis resistance - Kim, Young-Joo; Choi, Won-Il; Jeon, Bu-Nam; Choi, Kyung-Chul; Kim, Kunhong; Kim, Tae-Jin; Ham, Jungyeob; Jang, Hyuk Jai; Kang, Ki Sung; Ko, Hyeonseok (ELSEVIER IRELAND LTD, 2014)
The epithelial mesenchymal transition (EMT) is a pivotal cellular process during which epithelial polarized cells become motile mesenchymal-appearing cells, which, in turn, promotes the metastatic potential of cancer. Ginseng is a perennial plant belonging to the genus Panax that exhibits a wide range of pharmacological and physiological activities. Ginsenosides 20-Rg3, which is the active component of ginseng, has various medical effects, such as anti-tumorigenic, anti-angiogenesis, and anti-fatiguing activities. In addition, ginsenosides 20(S)-Rg3 and 20(R)-Rg3 are epimers, and this epimerization is produced by steaming. However, the possible role of 20(S)-Rg3 and 20(R)-Rg3 in the EMT is unclear. We investigated the effect of 20(S)-Rg3 and 20(R)-Rg3 on the EMT. Transforming growth factor-beta 1 (TGF-beta 1) induces the EMT to promote lung adenocarcinoma migration, invasion, and anoikis resistance. To understand the repressive role of 20(S)-Rg3 and 20(R)-Rg3 in lung cancer migration, invasion, and anoikis resistance, we investigated the potential use of 20(S)-Rg3 and 20(R)-Rg3 as inhibitors of TGF-beta 1-induced EMT development in A549 lung cancer cells in vitro. Here, we show that 20(R)-Rg3, but not 20(S)-Rg3, markedly increased expression of the epithelial marker E-cadherin and repressed Snail upregulation and expression of the mesenchymal marker vimentin during initiation of the TGF-beta 1-induced EMT. 20(R)-Rg3 also inhibited the TGF-beta 1-induced increase in cell migration, invasion, and anoikis resistance of A549 lung cancer cells. Additionally, 20(R)-Rg3 markedly inhibited TGF-beta 1-regulated matrix metalloproteinase-2 and activation of Smad2 and p38 mitogen activated protein kinase. Taken together, our findings provide new evidence that 20(R)-Rg3 suppresses lung cancer migration, invasion, and anoikis resistance in vitro by inhibiting the TGF-beta 1-induced EMT. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: TGF-BETA; TRANSFORMING GROWTH-FACTOR-BETA-1; CADHERIN EXPRESSION; CEREBRAL-ISCHEMIA; TUMOR-METASTASIS; SNAIL; MATRIX; CELLS; RG(3); GENISTEIN